Pratiques constitutives et connaissances contributives pour une compétence politique environnementale - Melki Slimani; Angela Barthes; Jean-Marc Lange (Éducation et Socialisation)
We propose an epistemological formalization of political competence, defined as an aptitude or disposition to carry out political action, here linked to the environmental field, with a view to proposing a method of analysis of university curricula. It is a question of understanding the components of a political competence in university curricula and of evaluating the curricular morphologies in terms of constituent practices and contributory knowledge.